Norms of Democracy and Human Rights Within ASEAN Non-Intervention Principle Analysis of FORUM-ASIA's Participation in Facilitating Dialogues for Humanitarian Conflict Resolution in Myanmar in 2021 - Nirmala, Ronna (Green Publisher Indonesia, 2023)
The paper elaborates on the challenges civil society coalitions face in advocating for democratic norms and human rights in humanitarian conflicts in Myanmar. The article discusses the challenges the coalition, FORUM-ASIA, encountered in dealing with the non-intervention principle of ASEAN countries. The analysis in this article utilizes the concept of transnational civil society (TCS) with a qualitative method involving document studies and media reports. While the dominant power and authority of the state undermine the influence of transnational actors in advocating for the interests of marginalized groups, the article argues that transnational networks and institutions must establish cultural and ideational foundations that encompass political and social interests to drive this transformative process successfully. Another significant aspect highlighted is how these actors function as media systems, both in traditional and contemporary forms, influencing public opinion and catalyzing social change.